2018
DOI: 10.3390/su10020372
|View full text |Cite
|
Sign up to set email alerts
|

Interannual Carbon and Nutrient Fluxes in Southeastern Taiwan Strait

Abstract: Abstract:The Taiwan Strait (TS) is one of the main sources of phosphate that supports the large fish catches of the phosphate-limited East China Sea (ECS). The Penghu Channel is the deepest part of the TS, and most of the flow of the TS towards the ECS is principally through this channel. Empirical equations that are based on measurements made during 19 cruises (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010)(2011) were combined with water velocity, salinity, and temperature, which were model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
2
8
0
Order By: Relevance
“…The seasonal variations of nutrients are strongly influenced by the seasonal change of different water mass occupation. Consequently, the seasonal change of water masses in the Taiwan Strait in this research is in accordance with previous research (Jan et al, 2002(Jan et al, , 2006(Jan et al, , 2010Chen, 2003Chen, , 2011Chen and Sheu, 2006;Wu et al, 2007;Chen et al, 2010;Huang et al, 2018). Hong et al (2011) revealed that there are three upwelling areas in the southern Taiwan Strait in summer.…”
Section: Water Masses Variety and Nutrients Availabilitysupporting
confidence: 91%
See 2 more Smart Citations
“…The seasonal variations of nutrients are strongly influenced by the seasonal change of different water mass occupation. Consequently, the seasonal change of water masses in the Taiwan Strait in this research is in accordance with previous research (Jan et al, 2002(Jan et al, , 2006(Jan et al, , 2010Chen, 2003Chen, , 2011Chen and Sheu, 2006;Wu et al, 2007;Chen et al, 2010;Huang et al, 2018). Hong et al (2011) revealed that there are three upwelling areas in the southern Taiwan Strait in summer.…”
Section: Water Masses Variety and Nutrients Availabilitysupporting
confidence: 91%
“…In addition, Jan et al (2010) found that the source water in the Taiwan Strait comes from the SCSW in summer. Huang et al (2018) also reported that during the summer and autumn, the main water mass in the Penghu Channel is the SCSW. Moreover, since precipitation is heavier in summer, water in the top layer is warmer and fresher during the summer than during the autumn (Huang et al, 2018).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Those estimates were calculated using chemical data from one or only a few cruises, and so may exhibit higher uncertainty than the data in this study based on 57 cruises. Our pervious study reported that the water, TA, DIC, N, P, and Si transports in the deepest part of the TS, Penghu Channel, are 0.81 ± 0.34 Sv, 1.87 ± 0.79 mmol C s −1 , 1.65 ± 0.71 mmol C s −1 , 1.20 ± 0.99 kmol N s −1 , 0.13 ± 0.085 kmol P s −1 , and 3.06 ± 1.83 kmol Si s −1 30 . Generally, the water and chemical transports in the TS are higher than those in the Penghu Channel except the N transport, and that reflects the substantial southward N transport by the CCC in the TS.
Figure 2Time series of ( a ) water, ( b ) TA, ( c ) DIC, ( d ) N, ( e ) P, and ( f ) Si model-calculated transports.
…”
Section: Resultsmentioning
confidence: 97%
“…To understand the exchanges between the ECS and the SCS, the study area covers cross-sections at both ends of the TS. Compared with our preliminary study which investigated the southeastern corner of the TS 30 , this investigation focuses on the interaction between the ECS and the SCS, and mechanisms affecting long-term variations in the TS.…”
Section: Introductionmentioning
confidence: 99%